Comparison of effective rate coefficients for high energy charge-exchange with measurements of the Rydberg series of Ar16+ at the tokamak TEXTOR. (4th June 2015) - Schlummer, T; Marchuk, O; Schultz, D R; Bertschinger, G; Biel, W; Reiter, D; TEXTOR-Team, the
Abstract: The charge-exchange (CX) rate coefficients for highly ionized impurity ions play a crucial role in fusion plasma diagnostics. However, till today a substantial difference exists in data for the n l -resolved cross-sections based on the different approximations underlying the classical trajectory Monte Carlo (CTMC) calculations either based on the standard initial momentum distribution of target electron orbits (pCTMC, as in the CX data provided by Whyte et al (1998 Phys. Plasmas 5 3694 ) and Schultz et al (2010 J. Phys. B: At. Mol. Opt. Phys. 43 144002 ) or based on the alternate initial radial distribution of orbits (rCTMC, as in the calculations of Errea et al (2006 J. Phys. B: At. Mol. Opt. Phys. 39 L91 ). In this paper, results of new pCTMC and rCTMC calculations for CX in 16.7, 25, and 50 keV/ u Ar 17+ + H(1s), H(2s), and H(2p) are compared against X-ray line measurements performed at the tokamak TEXTOR. The Rydberg series (1s n p–1s 2 ) and the K α -spectrum (1s2l–1s 2 ) of He-like argon were measured directly in the beam-line of a 16.7–50 keV/ u hydrogen injector. The intensities of the spectral lines are compared to the effective CX rate coefficients utilizing both sets of cross sections. While both data sets show good agreement with respect to the observed impact on the K α transition, only the pCTMC data allow a consistent description of the CX 'resonance' observed on the Rydberg lines around n ≈ 8, 9. Similar to the case of low energy ion–atom interactions reported from different tokamaks, the observed influence of CX is separable into contributions from beam particles in the ground and excited states, respectively. It is shown, that the number of beam excited states n h contributing to the CX signal, where n h is the principal quantum number, is limited to n h ≲ 10, confirming the results of recent collisional-radiative models of beam atoms in parabolic states.